PENGARUH VARIASI FRAKSI VOLUME KOMPOSIT SERAT E-GLASS ±45° POLYESTER 157 BQTN TERHADAP KEKUATAN BENDING DAN GESER - Istyawan Priyahapsara; Izza Rizky Assihhaly (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2017)
Demand of composite as aeronatics material is incresing. It’s light weight, high specific strength, are become a favour of research. Fiber volume Fraction (FVF) is one of important factor on making of composite. The volume ratio between FVF and the resin is affecting its mechanical properties. In this reaserach there were three ratio varation between fiber and the resin. Bending and shear test were conducted through out this research. Results show that, the ductility increased due to the increased of its ratio, but it’s shear stressare decresed.